E-Commerce Law - Chadha, Anu; Sudan, Amrik Singh; Gupta, Alka (Indian Journal of Marketing, 2004)
Electronic commerce has revolutionized the business activities. In order to speed up the work, organizations are gradually computerized and networks are being set up to share information. In this model the network first appeared within the organization. For any data to get added or to get out of this system, manual intervention was required. The next big step was the extensions of access of this network to suppliers. This is widely known as Electronic Data Interchange (EDI), which is the foundation of e-commerce. EDI is the computer-to-computer exchange of structured business information in a standard electronic format. Commerce is global but law-governing commerce is not globally uniform. Moreover, the old set of rules and practices governing communication and trading are largely incompatible with the emerging system of communication and trading practices in a borderless world created by the Internet.